2009
DOI: 10.1093/rheumatology/kep178
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and severity of rheumatoid arthritis at diagnosis in Senegal

Abstract: The diagnosis of RA is delayed in Senegal, and the disease is highly active at diagnosis, although 44 patients have no erosions, and extra-articular manifestations are rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
17
1
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 15 publications
7
17
1
6
Order By: Relevance
“…The rheumatoid factor, present in 78% of the British patients has only been found in 48% of Nigerians [20]. In the recent publications in this African region, we note a rise of the impact and the seriousness of the illness, even though a lower frequency [25]. These data agree with those of the western literature [1].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The rheumatoid factor, present in 78% of the British patients has only been found in 48% of Nigerians [20]. In the recent publications in this African region, we note a rise of the impact and the seriousness of the illness, even though a lower frequency [25]. These data agree with those of the western literature [1].…”
Section: Discussionsupporting
confidence: 90%
“…The strong seropositivity to the rheumatoid factor (54.5%) and to the anti-CCP antibodies (89.2%) noted in this study was also reported by Ndongo (rheumatoid factor: 78% and anti-CCP: 90%) [25] and by Ouédraogo (rheumatoid factor: 70% and anti-CCP: 80%) [24]. In the western literature we note the prevalence of the factor and superimpose able antibodies anti-CCP to these data [29] [30] [31].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Adewolo et al [18] observed that in 200 patients followed for RA in Nigeria only 38.5% were RF positive and 29% had joint erosions on radiographs of hands, while the average duration of symptoms was 63 months before the first consultation. Ndongo S et al [19] in Senegal reported that joint erosions were present in one-third of patients and that extra-articular manifestations were very rare, while the average time from the onset of symptoms to initiation of disease modifying antirheumatic drugs was 54 months. Anaya JM et al [20] in Colombia have described that RA was less severe in blacks than Mestizos in terms of radiographic damage.…”
Section: Discussionmentioning
confidence: 99%